Protocols for management of oral complications of chemotherapy and/or radiotherapy for oral cancer: Systematic review and meta-analysis current - Carneiro-Neto, Josï¿½-Nunes [UNESP]; de-Menezes, Juliana-Dreyer-da-Silva [UNESP]; Moura, Lucas-Borin [UNESP]; Massucato, Elaine-Maria-Sgavioli [UNESP]; de-Andrade, Cleverton-Roberto [UNESP] (Medicina Oral, S.L., 2017)
Background and Objectives: Considering the high possibility of dentist consult a patient with oral complications of chemotherapy and/or radiotherapy for oral cancer because of the advances in this area, this study aims to systematically review the literature to identify and suggest effective and safe protocols for the managements of oral complications in oncology patients. Material and Methods: The systematic review was designed by PICO and PRISMA including eligibility and exclusion criteria; the source of information and search strategy in PubMed according MeSH: “Mouth Neoplasms and Radiotherapy” and “Mouth Neoplasms and Drug Therapy” the period from 2010 to 2015; selection and data collection of study was carried form blind and independently by two researchers; risk of bias and methodological quality: ensured by the PEDro scale; synthesis of data: of oral complications were evaluated by adapted version of associative direction classification proposed by Costigan and collaborators; and data analysis was performed by the meta-analysis of BioEstat program (5.0) in the included studies. Results: 2,700 articles found, 2,371 were selected after removal of duplicate and elected 40 full-text articles. Of these, only 06 articles were included in the systematic review with exclusion of others, per obtain punctuation ≥ 7 with high methodological quality for synthesis of the managements of oral complications. Since 05 articles were associated with low risk of bias composing the protocols suggestive for managements and the meta-analysis in odds ratio (0.916) to cure and relative risk (1.049) for the development of oral mucositis and pain. Conclusions: The protocols suggestive for managements of oral mucositis and pain with MuGard - mucoadhesive hydrogel; PerioAid Tratamientoï¿½ antiseptic mouthrinse with chlorhexidine and cetylpyridinium chloride; Episilï¿½ plus benzydamine - bioadhesive oromucosal gel; 0,03% of Triclosan mouthwash Colgate Plax; and Diode Laser Therapy of low-level are safe for oncology patients applied according to adopted clinical parameters.
Keywords: Chemotherapy; Complications; Management; Oral cancer; Radiotherapy